Development of a Warehouse Performance Measurement Framework for PT X Using the Warehouse Key Performance Indicators (WKPI) Model - Eka Nabila Permatasari; Iwan Vanany (Journal of Social Research, 2026)
This study aims to develop a warehouse performance measurement framework and measure the performance of PT X’s warehouse using the Warehouse Key Performance Indicators (WKPI) model, as the warehouse previously lacked a structured performance measurement system. A screening process was conducted on 41 WKPI indicators, resulting in 10 indicators that were considered relevant to the warehouse operations. The indicators were weighted using the Analytical Hierarchy Process (AHP), while warehouse performance was measured using the Snorm De Boer Scoring System. Furthermore, the Traffic Light System (TLS) was employed to classify the level of performance achievement. The results indicate that the quality dimension obtained the highest weight among all dimensions. The performance measurement generated an average warehouse performance score of 85.71%, indicating that the overall performance of PT X’s warehouse was satisfactory. However, the TLS analysis revealed that order picking time and order lead time remained in the red category, indicating the need for performance improvement. Therefore, Root Cause Analysis (RCA) was conducted to identify the underlying causes of the performance gaps and to formulate improvement recommendations. The proposed improvements are expected to enhance the operational performance of the warehouse.